Pojmovanje časa in prostora ter kozmologija v poeziji in poetiki Gregorja Strniše - Žižek Urbas, Andreja (Jezik in slovstvo, 2004)
The poetry and poetics of Gregor Strniša were created in a gradual and syncretic process, based on the meeting point philosophy, mythic thought and the natural sciences, in particular cosmology. He introduced scientific principles into his literary hermeneutics, such as the specific and general theory of relativity and the principle of indererminism, while in his own way, he also answered the speculative theories of good harmoy of the universe,and the anthropic principle of the universe. His collections of poetry, the most prominent being the last five (Želod or Acorn in English, Oko or Eye, Škarje or Scissors, Jajce or Egg, and Vesolje or Universe), can be understood as cosmological models, since they built on the basis of thought-out compositional principles, which over and over again define place and time. For Strniša, science and poetry are two possible routes towards the comprehension of the universe, thruth, everythig; unfortunately, his poetry remains too enigmatic and hermetic for many readers.
Keywords: Strniša, Gregor, 1930-1987; Slovene literature; slovenska književnost; slovenska poezija; 20.st.; čas; prostor; kozmologija; literarne študije